Superovulation Response, Embryo Recovery and Quality in Sahiwal Cows and Heifers - SIDDIQUl, M U; PANCHAL, M T; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
Superovulation response, embryo recovery and quality in Sahiwal cows and heifers were studied in12 animals divided in two grmips (Group A: 6 Sahiwal cows and Group B: 6 Sahiwal heifers). Forinduction of superovulation, FSH-P (Folltropin-V, Bioniche Animal Health, Canada, @ 200 mg perdonor in 8 equally divided doses of 1.25 ml each) ,vas administered i.m. over four days at 12 hr interval,starting day 9 -11 post estrus. A single dose of PGF2a (lliren, lntervet,@ 5 ml) was given i.m. 48 hr afterthe first FSH injection, to bring the donors in heat. First A I was done 48 hr after PG injection, followedby two more inseminations at 12 hr intervals. On day 7 of first Al, all the donors were flushed forembryo recovery. Among 6 Sahiwal cows (Group A), only 3 (50.00%) responded to FSH treatment withthe total number of CL to be 17 (5.67/donor) and a total of 10 (3 viable and 7 degenerated) embryos. Themean recovery of total and viable embryos (VE) for responded donors and overall were found to be 3.33and 1.00 and 1.67 and 0.50 embryos per flush, respectively. All Sahiwal heifers (Group B) responded toFSH treatment with the total number of CL to be 50 (8.33/donor) and a total of 37 ( 18 VE; 2 UFO; 1zona and · 16 degenerated) embryos. The mean recovery of total and viable embryos was found to be 6.17and 3.00 embryos per flush, respectively. Sahiwal heifers (Group B) yielded comparatively highernumber of mean ovulations (8.33) and embryos, both total (6. I 7) as well as viable (3.00), than those ofthe cows under Group A (3.17, 1.67 and 0.50, respectively). Based on the results obtained, it wasconcluded that since Sahiwal heifers had much better supersovulation response to gqnadotrophintreatment and higher recovery of total and viable embryos as compared to Sahiwal cows, heifers can beused as potential embryos donors.
Keywords: Superovulation; Embryo recovery; Sahiwal cows